The ionic reordering in Fe-Ti ferrimagnetics as a dominant source of the reversed RM in basaltic rocks - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2009)
The  basalts of  the Pleistocene to Quaternary age  from  southern  part of Slovakia  were  investigated.  These  are  the basalts containing  predominantly  the titano- maghemites (Ti-Mgh-es) which  carry  the  reversed  remanent  magnetization (RM).  The partial thermoremanent magnetization (PTRM) in original  and artiﬁcially prepared sam- ples was induced  in the geomagnetic ﬁeld of normal  polarity and intensity H ≈ 48μT.  The PTRM reversed  by the  self-reversed  mechanism was induced  in all the  above-mentioned types  of basalts, in the interval  300 to 475 °C.  In  this  temperature  interval  an  increase of magnetic susceptibility with  a peak about 450 °C was detected. The  acquired reversed RM and  PTRM of basalts have been explained on the basis of the reordering of magnetic ions in the A and  B sub-lattices of the oxidized  Fe-Ti  ferrimagnetics in basalts.